L’histoire sainte de Fontenelle. Une lecture des Gesta abbatum - Pascal Pradié (Tabularia)
If the Acts of the holy abbots of the monastery of Fontenelle represent in many ways an important source of historical information, they should not make us forget that they were written in a monastic context, with a spiritual intent proper to the literary genre of the Gesta.